Exploring the Skills Prioritised in the Assessment of Students Pursuing Adult Nursing, Post‐COVID: A Qualitative Analysis - Carmel Bond; Joanna M. Painter; Donna Barnett (Nursing Open)
ABSTRACT Aim To explore comments made by registered nurse practice assessors during the clinical assessment of students pursuing adult nursing. Background Student nurses are entering a workforce that has changed professional and educational nursing practice systems due to the COVID‐19 pandemic. Limited placement learning during lockdowns reduced opportunities for students to practise clinical skills in person. However, the current state of practice assessment for students pursuing adult nursing, particularly post‐COVID, has yet to be explored. Design Qualitative content analysis. Methods Data were collected from the online assessment documentation of second‐year BSc students pursuing adult nursing. A qualitative content analysis was performed to analyse comments made by qualified adult nurses who are positioned as clinical practice assessors for students pursuing adult nursing. COREQ reporting guidelines were followed. Results Two main themes were identified: (1) task‐focussed competencies and (2) relational aspects of care. Task‐focussed competencies included ‘technically complex physical health skills’ with an emphasis on specialist clinical interventions and procedures. Relational aspects of care included values‐based attributes such as compassion and empathy. However, relational aspects of care were noted less frequently. Comments related to communication skills and values‐based care were less diverse than those relating to technical tasks and the language used was perfunctory. Conclusion Adult nursing assessments emphasise technical, task‐focused competencies, with less attention given to relational skills like compassion and communication. To address this gap, nursing education must better integrate relational and technical competencies, enhancing patient care and supporting nurses' mental health and wellbeing for a more holistic post‐pandemic nursing practice. Implications for Practice Results suggest an increased focus on the development of relational skills is needed for students pursuing adult nursing. Patient or Public Contribution No patient or public contribution.